SISTEM IRIGASI SUBAK DENGAN LANDASAN TRI HITA KARANA (THK) SEBAGAI TEKNOLOGI SEPADAN DALAM PERTANIAN BERIRIGASI - Wayan Windia; Suprodjo Pusposutardjo; Nyoman Sutawan; Putu Sudira; Sigit Supadmo Arif (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Subak system is a custom law community with socio-technical-religious characteristics,consists of a group of farmers that manage irrigation water at their irrigarted area (sawah).The existance of subak irrigation systems are dynamic, due to the socio-cultural conditionsof the society. Subak as a irrigation system which is based on Tri Hita Karana (THK)concept, is implemented on the system of irrigation in Bali. Its based on socio-technicalconcept which technologically integrated with the socio-cultural of the society.Furthermore, the form of subak system as an appropriate technology, is implemented onthe form of thinking-pattern, social system, and the development of artefax of the system.The final goals of the system are in order to achieve the harmony and togetherness in theirrigation management.